PENGARUH KUALITAS LAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN TOKO SERBA ADA MATAHARI DI PONDOK GEDE PLAZA KOTA BEKASI - Adista Fitriani; Iwan Kurniawan Subagja (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
Business competition is currently increasingly stringent requires that marketers develop marketing strategy that is telling. Companies that win business competition can solidify the company's position to survive in the future. This research study aims to analyze the effect of service quality and customer value on customer satisfaction of Multipurpose Shop Matahari in Pondok Gede Plaza simultaneously and partially. The study population is all customers of multipurpose store Matahari. This research uses multiple linear regression analysis technique, with survey data and questionnaire to 130 respondents. The results of this study indicate that the quality of service and customer value positively and significantly affect the customer satisfaction, service quality and customer value positively and partially significant to customer satisfaction.